(1)
(f+g)(x) = 6x^2+2x-7+4x-3=6x^2+6x-10
(f-g)(x)=6x^2+2x-7-4x+3 = 6x^2-2x-4
(2)
(f+g)(x)=2x-3x+1-2x=-3x+1
(f-g)(x)=2x-3x-1+2x=x-1
Answer:
2a + 10
Step-by-step explanation:
the number = 2(a + 5)
= 2a + 10
Answer:
IJK and KJM
Step-by-step explanation:
Vertical Angles are the angles opposite each other when two lines cross
they are always equal in measure and share a point (in this case J)
hope this helps
Check the picture below
the triangles are similar, the angles are congruents then
so... just add them up, and divide by 2, or set them as rational
<span>Just graph the function up to and/or including the points indicated.
- if you have a piecewise function defined as y=x when x < 0
y=-x when x >=1
You would graph y=x from the negative direction up to 0 (but leaving an open circle on 0 because the function is not defined there
Then start at point 1 (this time with a closed circle because y=-x is defined at 1, and graph y=-x.</span>